Effects of Low-Cost Repair Techniques on Restoration of Mechanical Properties of Fire-Damaged Concrete - Noman, Muhammad; Yaqub, Muhammad; Abid, Muhammad; Musarat, Muhammad Ali; Vatin, Nikolai Ivanovich; Usman, Muhammad (Frontiers in Materials, 2022)
Researchers have conducted numerous investigations on various repair techniques to restore the mechanical properties of fire-damaged concrete. However, most of the techniques are either expensive or require high technical skills. As a continuous work, this study involved an experimental investigation of the effects of various low-cost repair techniques to restore the mechanical properties of fire-damaged concrete. Sixty cylindrical concrete samples were subjected to heat ranging from 400°C to 800°C in a propane gas furnace. The samples were categorized into six groups, including; undamaged, fire damaged, fire damaged and repaired using water curing, fire damaged and repaired using cement-based slurry injection, and re-curing fire damaged and repaired with steel wire mesh along with epoxy resin wrapping, and fire-damaged and repaired using epoxy injection. The samples were tested for non-destructive and destructive tests, including ultrasonic pulse velocity, rebound hammer, and compressive strength. The results showed that the use of cement-based slurry injection along with the water-curing repair technique could regain almost 90% of its ultimate strength and secant stiffness, making it the most effective low-cost repair technique for fire-damaged concrete exposed up to 700°C.